Implementation of Talking Stick Method on Acid-Base Concepts to Improve Students' Critical Thinking Skills - Azzahra, St Fatimah; Simatupang, Nova Irawati (International Journal of STEM Education for Sustainability, 2021)
This study aimed to improve the critical thinking skills of class XI high school on acid base material in the 2018/2019 using the talking stick method. This research is a classroom action research conducted in two cycles. Each cycle consists of planning, implementation, observation and reflection so that this study describes planning, activities and improving critical thinking skills of high school of class XI. The subjects of this research is all students of grade XI in one of the South Tangerang high schools in Indonesia which consisted of 33 students. Data collection techniques in this study were using essay tests, observation sheets, teacher activities, student activities, field notes and interviews. The results of this study indicate that students’ critical thinking skills increase using the talking stick method seen from the student ability to answer questions, express opinions, respond to friend opinions and consider sources. Critical thinking skills has increased, in the first cycle that is equal to 21.20% while in the second cycle is 90.90%. It can be concluded that the use of the talking stick method can improve the critical thinking skills of class IX high school in acid base material.